A CASE OF HEAVY FISH MORTALITY IN THE RIVER SONE AT DEHRI-ON-SONE, BIHAR, CAUSED BY THE WASTES OF THE ROHTAS INDUSTRIES LTD., DALMIANAGAR - Banerjea, Santimoy; Motwani, M P; Karamchandani, S J (Indian Journal of Fisheries, 2015)
Adverse physico-chemical conditions, incident to the oxidative decay of the bottom deposits or of thick algal growth, are commonly encountered in confined waters Hke those of lakes, ponds and tanks, fesulting in mortality of fish. Sometimes toxic products of algal decomposition, released directly in the water, also take a heavy toll of fish (Sewell, 1926; Pruthi, 1932; Prescott, 1948; Ganapati et al., 1950; Banerjea, unpublished). Such conditions, however, rarely obtain in fluviatile waters like rivers and streams where the phenomenon of self-purification plays an important role in combating such adverse conditions. The rivers, on the other hand, are exposed to industrial pollution. The chemical and other industrial factories, generally producing a considerable quantity of Uquid wastes, are mostly built adjacent to the rivers and utilise these watercoiirses for the easy and cheap disposal of their waste effluents. The indystriail wastes may be directly or indirectly injurious to fish life of the receiving rivers and it is not uncommon to find such tracts; of the rivers becoming dejpleted of their once good fisheries